A large ongoing outbreak of hepatitis A predominantly affecting young males in Lazio, Italy; August 2016 - March 2017 - Lanini, Simone; Minosse, Claudia; Vairo, Francesco; Garbuglia, Annarosa; Di Bari, Virginia; Agresta, Alessandro; Rezza, Giovanni; Puro, Vincenzo; Pendenza, Alessio; Loffredo, Maria Rosaria; Scognamiglio, Paola; Zumla, Alimuddin; et al. (PloS one, 2017)
The hepatitis A virus (HAV) is mainly transmitted through the faecal-oral route. In industrialized countries HAV infection generally occurs as either sporadic cases in travelers from endemic areas, local outbreak within closed/semi-closed population and as foodborne community outbreak. Recently, an increasing number of HAV infection clusters have been reported among young men-who-have-sex-with-men (MSM). The Lazio Regional Service for the epidemiology and control for infectious diseases (SeRESMI) has noticed an increase of acute hepatitis A (AHA) since September 2016. Temporal analysis carried out with a discrete Poisson model using surveillance data between January 2016 and March 2017 evidenced an ongoing outbreak of AHA that started at the end of August. Molecular investigation carried out on 130 out of 513 cases AHA reported until March 2017 suggests that this outbreak is mainly supported by an HAV variant which is currently spreading within MSM communities across Europe (VRD_521_2016). The report confirms that AHA is an emerging issue among MSM. In addition through the integration of standard (case based) surveillance with molecular investigation we could discriminate, temporally concomitant but epidemiologically unrelated, clusters due to different HAV variants. As suggested by the WHO, in countries with low HAV circulation, vaccination programmes should be tailored on the local epidemiological patterns to prevent outbreaks among high risk groups and eventual spillover of the infection in the general population.